YURISPRUDENSI HUKUM PENYELESAIAN SENGKETA KEWARISAN BEDA AGAMA DI PENGADILAN AGAMA PERKARA NOMOR 0042/Pdt.G/2014/PA.Yk DAN PUTUSAN KASASI NOMOR 218/K/Ag/2016 - Zikri, Muhammad; Sukiati; Harahap, Mhd Yadi (IAIN Ambon, 2025)
The inheritance dispute in Supreme Court Decision Number 218 K/Ag/2016 highlights the complexity of applying Islamic inheritance law in a pluralistic society, particularly when religious differences exist between the deceased and the parties claiming inheritance rights. The conflict arose when the estate of a Muslim decedent was claimed and controlled by non-Muslim relatives. The plaintiffs, who were the decedent’s paternal half-siblings, filed a lawsuit in the Religious Court, arguing that the defendants, being Catholic, were not entitled to inherit under Islamic law. Additionally, the plaintiffs alleged that the land certificate was obtained unlawfully through falsified documents, making its legal validity questionable. This study employs a normative juridical method, utilizing statutory and case approaches. The data were collected by reviewing court decisions from the first instance to the appellate and cassation levels. A qualitative analysis was conducted to examine the judges’ legal reasoning and the application of Islamic inheritance principles. The findings indicate that religious conformity between the deceased and the heirs is a fundamental requirement in Islamic inheritance law. A difference in religion constitutes a legal barrier to inheritance (mawānī al-irth), reaffirming that non-Muslims cannot inherit from Muslims according to Islamic legal doctrine Keywords: jurisprudence, inheritance, different religions